A conceptual model of factors affecting e-procurement usage among Jordanian firms - Daouda, Luay; Ibrahima, Marhaiza (IJRDO - Journal of Business Management, 2017)
E-procurement is an organizational application of IT used in setting up agreements, facilitating the Business to Business (B2B) procuring transactions for goods and services, and requesting price quotations. This study explains a plan examining the organizational level e-procurement practice from two perspectives- information and transaction. This study also investigates the TOE determinants that influence e-procurement applications in Jordanian firms and the financial performance of such applications. Even though e-procurement offers significant advantages, Jordanian firms with e-procurement capability are not applying e-procurement for a substantial percentage of their transactions. Using the Technology, Organization, and Environment (TOE) framework, the Diffusion of Innovations (DOI) theory, and the Resource-based view (RBV) theory, an integrated model is formed. The e-procurement application is assumed to be affected by the technological context (relative advantage, compatibility, and complexity), organizational context (organizational readiness, top management support and information system committee), and environmental context (competition pressure and rules and regulations).